DIGITAL MARKETING STRATEGIES FOR ENHANCING COMPETITIVE POSITIONING OF RETAIL CHAINS - Matyakubova , Aziza (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
This thesis investigates digital marketing strategies for enhancing competitive positioning of retail chains in Uzbekistan based on comprehensive analysis of 214 retail chain outlets across 8 major cities during 2021-2024 and customer behavioral data from 4,782 consumers.